2022
DOI: 10.3390/cells11162602
|View full text |Cite
|
Sign up to set email alerts
|

Optical Monitoring in Neonatal Seizures

Abstract: Background: Neonatal seizures remain a significant cause of morbidity and mortality worldwide. The past decade has resulted in substantial progress in seizure detection and understanding the impact seizures have on the developing brain. Optical monitoring such as cerebral near-infrared spectroscopy (NIRS) and broadband NIRS can provide non-invasive continuous real-time monitoring of the changes in brain metabolism and haemodynamics. Aim: To perform a systematic review of optical biomarkers to identify changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 126 publications
(230 reference statements)
0
11
0
Order By: Relevance
“…In our study, seizures were only detected in the HI group in three out of eight animals. Seizures have been shown to elicit changes in cerebral metabolism and hemodynamics in both animal and human neonates detectable through optical monitoring ( 51 , 52 ). In contrast, we detected no change in oxygen tension, rSO 2 , CBF, or ICP in relation to seizures.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, seizures were only detected in the HI group in three out of eight animals. Seizures have been shown to elicit changes in cerebral metabolism and hemodynamics in both animal and human neonates detectable through optical monitoring ( 51 , 52 ). In contrast, we detected no change in oxygen tension, rSO 2 , CBF, or ICP in relation to seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Neurovascular (and neurometabolic) dynamics is also relevant to adult acute brain injury cases, where normalization of neurovascular coupling may herald recovery of consciousness ( 56 ). Here, the effects of seizure activity on the coupling dynamics of the neural activity (measured with EEG) with the cerebral metabolism, oxygen delivery, and blood volume may be crucial to guide medication ( 36 , 57 ), especially by leveraging optical monitoring in neonates ( 58 ). Other relevant chromophores, cytochrome c oxidase (CCO) and water, can also be investigated with optical monitoring in the neonates ( 58 ), which was developed in another study by adding four different wavelengths (780, 810, 820, and 840 nm) to the low-cost EEG-fNIRS sensor ( https://neuromodec.org/nyc-neuromodulation-online-2020/P18.html ) ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, the effects of seizure activity on the coupling dynamics of the neural activity (measured with EEG) with the cerebral metabolism, oxygen delivery, and blood volume may be crucial to guide medication ( 36 , 57 ), especially by leveraging optical monitoring in neonates ( 58 ). Other relevant chromophores, cytochrome c oxidase (CCO) and water, can also be investigated with optical monitoring in the neonates ( 58 ), which was developed in another study by adding four different wavelengths (780, 810, 820, and 840 nm) to the low-cost EEG-fNIRS sensor ( https://neuromodec.org/nyc-neuromodulation-online-2020/P18.html ) ( 59 ). In that case series ( 59 ), we found that neurometabolic coupling was specifically affected in HIE with sepsis, which may be related to the differences in the stabilization diagrams (see Figure 5 ) between the six severe HIE human perinatal cases and the four severe HIE human perinatal cases with sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations